Ethics in Transaction Cost Economics - Da Veiga, M. R.; Major, M. (5th Symposium on Ethics and Social Responsibility Research, 2019)
Purpose: This paper provides an Aristotelian virtue ethics analysis of decisions regarding the UN internal oversight governance structures focused on Transaction Cost Economics (TCE) theory. Design/methodology/approach: We explore “probity” and “independence” transactions’ attributes through historical narrative case-based research to answer the question – Why did consecutive executive decisions to strengthen internal oversight structures not relieve “probity” hazards? Findings: Our analysis shows that at the UN increased oversight governance structures, i.e. incentives, did not relieve probity/ethics hazards as predicted in TCE (Williamson, 1999). It follows that executive powers as well as overseers systematically trumpeted the UN “rules of the game”, breaching probity/ethics and disregarding the oversight independence prerogative and the UN Charter, failing to contribute to the “common good” and to protect the UN mission. It also follows that, as it stands now, the UN´s governance system does not accord full independence to the internal oversight: the Secretary-General is positioned in constant conflict of interest by virtue of the powers granted by the UN Charter. This deffective institutional design may be aggraveted whenever the Secretary-General behaves opportunistically. Originality/value: First time application of Williamson’s Public and Private Bureaucracies TCE. We find that TCE should be modified to include “virtue ethics” behavioral assumption as a transaction costs’ reduction device and explanatory framework for ethical failures, abandoning the opportunism behavioral assumption.